Analysis of Student Learning Outcomes on Biology of The Blood Circulation System in Senior High School - Jumrodah; A’in, Latifah Nur; Firanti, Tamaya (Islamic Journal of Integrated Science Education (IJISE), 2024)
The importance of analyzing the learning process becomes a very significant impetus when it is considered a process of changing student behavior. Evaluation is the process of collecting, assessing, and interpreting data to ensure the level of achievement of a student's learning goals. This study aims to determine student learning outcomes on circulatory system biology material class XI Senior High School. The method used in this study is the quantitative descriptive method. The result of this study is that the average score obtained by students after doing the question is 30.54 with the highest score of 56 points and the lowest score of 12 points. Of the 11 students who did 25 test questions, three students with the highest rankings and three students with the lowest rankings were obtained. Based on the results of research that has been carried out, it can be concluded that students have a good interest in learning the material of the circulatory system. However, some students are still unable to understand the material due to the lack of precise selection of learning methods and media applied by teachers in the learning process.